Флюїди глибинних горизонтів літосфери: зв'язок з родовищами нафти і газу в земній корі (за даними вивчення включень у мінералах глибинного походження) - Наумко, І.М.; Бекеша, С.М.; Сворень, Й.М. (Видавничий дім "Академперіодика" НАН України, 2008)
We have confirmed the influence of the processes of defluidization of deep-seated horizons of the lithosphere upon the formation of hydrocarbon-containing compounds in the medium of a deep-seated high-temperature fluid and have determined the connection of the mantle fluids as a source of the initial substance of hydrocarbons with oil and gas deposits in the Earth’s crust. This promotes the development and introduction of new non-traditional methods of forecast of the presence of oil and gas in a geological slit based on such defects in solid bodies as fluid inclusions.